Validation of IASI Satellite Ammonia Observations at the Pixel Scale Using In Situ Vertical Profiles. Issue 9 (3rd May 2021) - Guo, Xuehui; Wang, Rui; Pan, Da; Zondlo, Mark A.; Clarisse, Lieven; Van Damme, Martin; Whitburn, Simon; Coheur, Pierre‐François; Clerbaux, Cathy; Franco, Bruno; Golston, Levi M.; Wendt, Lars; et al.
Abstract: Satellite ammonia (NH3 ) observations provide unprecedented insights into NH3 emissions, spatiotemporal variabilities and trends, but validation with in situ measurements remains lacking. Here, total columns from the Infrared Atmospheric Sounding Interferometer (IASI) were intercompared to boundary layer NH3 profiles derived from aircraft‐ and surface‐based measurements primarily in Colorado, USA, in the summer of 2014. IASI‐NH3 version 3 near real‐time data set compared well to in situ derived columns (windows ±15 km around centroid, ±1 h around overpass time) with a correlation of 0.58, a slope of 0.78 ± 0.14 and an intercept of 2.1 × 10 15 ±1.5 × 10 15 molecules cm −2 . Agreement degrades at larger spatiotemporal windows, consistent with the short atmospheric lifetime of NH3 . We also examined IASI version 3R data, which relies on temperature retrievals from the ERA Reanalysis, and a third product generated using aircraft‐measured temperature profiles. The overall agreement improves slightly for both cases, and neither is biased within their combined measurement errors. Thus, spatiotemporal averaging of IASI over large windows can be used to reduce retrieval noise. Nonetheless, sampling artifacts of airborne NH3 instruments result in significant uncertainties of the in situ‐derived columns. For example, large validation differences exist between ascent and descent profiles, and the assumptions of the free tropospheric NH3 profiles used above the aircraft ceiling significantly impact the validation. Because short‐lived species like NH3 largely reside within the boundary layer with complex vertical structures, more comprehensive validation is needed across a wide range of environments. More accurate and widespread in situ NH3 data sets are therefore required for improved validations of satellite products. Plain Language Summary: Ammonia is an important species in the atmosphere that contributes to PM2.5 formation, but it is challenging to measure. The major source of ammonia is agricultural activities. Improving our estimate of ammonia emissions requires widespread and frequent measurements such as those from satellite. To date, satellite‐based ammonia measurements have not been extensively validated, particularly on the scale of individual measurements. We have compared satellite ammonia measurements with those from ground‐based and aircraft measurements and show that satellite measurements are accurate at the scale of an individual pixel. However, we also show that it is important to consider the spatial and temporal differences between the measurement scales (satellite vs. ground‐ and aircraft‐based) in regions where ammonia is concentrated and large sources exist. Improved validations will require advances in airborne ammonia measurement technologies, particularly for the relatively low levels of ammonia that exist above the boundary layer or away from strong sources. Finally, additional airborne‐based measurements are needed to compare to satellite‐based measurements in other regions and seasons to extend these conclusions to a global scale. Key Points: Infrared Atmospheric Sounding Interferometer NH3 columns agree well with those derived from boundary layer, in situ measurements with no significant biases at the pixel scale Validation in a hotspot region shows best agreement at narrow spatiotemporal scales on the order of the pixel size and mean transport time Additional accurate, airborne‐based NH3 data sets are critically needed for improved validations across a range of environments